ONLINE ENGLISH LEARNING DURING COVID-19 PANDEMIC: MOTIVATING AND DEMOTIVATING FACTORS AMONG EFL STUDENTS - Priscilla Tabitha; Y. G. Harto Pramono (Magister Scientiae, 2022)
Since pandemic novel outbreak, almost all educational institutes have transitioned to online learning in order to keep the teaching and learning process going. In Indonesia, the practice of online learning is still relatively, unclearly understood due to the minimum awareness of the ICT (Information and Communication Technology). Some studies revealed that online learning gave positive as well as negative impacts to the students’ learning motivation. Especially, the negative impacts may cause difficulties, stress, and anxiety in learning. Therefore, this present study was intended to reveal the factors affecting motivation and demotivation for students in learning English online, more specifically, during COVID-19 pandemic and to find out which factors were the most motivating and the most demotivating. A survey design was employed in this study. Thirty-six students of an English education study program at a private university were involved. The data were collected using questionnaire and analysed using statistic descriptive technique. The findings revealed that students’ motivation and demotivation could have been influenced by intrinsic and extrinsic factors. In particular, there were 5 motivating factors affecting students’ motivation, namely: students’ intrinsic learning motivation, self-efficacy, teachers’ performances & attitudes, contents & materials, and classmates’ attitudes. Among 5 motivating factors, teachers’ performances & attitudes turned out to be the most motivating factors, followed by contents & materials, and students’ intrinsic learning motivation. Concerning the demotivating factors, only one factor, i.e., technical factor was found to be the only one and most demotivating factor. This study contributes to the learning of  English during online as well as offline schools